2013
DOI: 10.1002/app.39681
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent pyrolytic product evolution profile for polyethylene terephthalate

Abstract: In this study, a detailed gas chromatographic study of pyrolysis products of polyethylene terephthalate (PET) has been carried out over a wide range of temperature (200-600 C). At low pyrolysis temperatures (200-300 C), yield of lighter hydrocarbons (C5-C10) is low; this gradually increases until maximum decomposition temperature (435 C) and decreases thereafter. At low temperature, PET essentially decomposes by ionic mechanism. However, at higher temperature, it may also proceed by radical mechanism. The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The decomposition mechanism of thermoplastic polyesters consists of an hererolytic scission via a six-membered ring intermediate, where the hydrogen from a β-carbon to the ester group is transferred to the ester carbonyl, followed by scission at the ester links, producing compounds with carboxylic and vinyl end groups [79]. It has been also reported that, at higher pyrolysis temperatures, radical (homolytic) degradation pathways may also occur [80]. The third degradation stage was located between 500–600 °C, being mainly related to char decomposition as well as degradation of the remaining lignin [63].…”
Section: Resultsmentioning
confidence: 99%
“…The decomposition mechanism of thermoplastic polyesters consists of an hererolytic scission via a six-membered ring intermediate, where the hydrogen from a β-carbon to the ester group is transferred to the ester carbonyl, followed by scission at the ester links, producing compounds with carboxylic and vinyl end groups [79]. It has been also reported that, at higher pyrolysis temperatures, radical (homolytic) degradation pathways may also occur [80]. The third degradation stage was located between 500–600 °C, being mainly related to char decomposition as well as degradation of the remaining lignin [63].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is assumed that radical decomposition of PE and PP was enhanced in the presence of PET. Radical species from the homolytic scission of carboxyl-ethylene glycol units ( COOC 2 H 4 ) in PET could occur at the present temperature (Scheme 2) [28], these species might have transferred to other plastics, causing chain length reduction. Additionally, ethylene glycol units could have been attacked by radical species derived from other plastics, producing gas compounds.…”
Section: Mixing Effects Of Plasticsmentioning
confidence: 99%
“…Pyrolysis of PET was studied using this analytical technique to investigate these conditions mentioned above, which are required in the tubular reactor (Dhahak et al 2019). Divinyl terephthalate, mono-vinyl terephthalate, benzene, toluene and terephthalic acid were the primarily identified products at 435 °C temperature pyrolysis using thermogravimetric analysis-mass spectroscopy analysis (Hujuri et al 2013). It is further explored by Liu et al (2018b) to detect the volatile organic compounds composition during the thermal degradation of PET fibres and popcorn.…”
Section: Thermogravimetric Analysis-mass Spectroscopymentioning
confidence: 99%